CORPORATE INFLUENCE AND MEDIA INTEGRITY: NAVIGATING COMMERCIAL PRESSURES IN JOURNALISM - Abid Ali; Waleed Ahmad; Muhammad Ali Malik (International Journal of Contemporary Issues in Social Sciences, 2024)
When corporate or political interests influence or control news content, it is known as media capture and undermines journalistic independence. This phenomenon, especially commercially induced capture, is becoming more common in Pakistan, where a few numbers of corporations control a large portion of the media landscape due to considerable media market concentration. Pakistan Tehreek-e-Insaf (PTI), the Pakistan People’s Party (PPP), the PML-N, and corporate businessmen are key actors in this scenario. Though the effects for public trust and democratic debate are dire, the ways in which economic interests shape media practices and content are still largely unstudied. By evaluating the challenges faced by individual journalists, their approaches to managing corporate influences, the public’s understanding of media capture, and its effects on public confidence in mainstream media, this study seeks to close this knowledge gap. Additionally, it looks into the dynamics of stakeholders where business and political interests converge, thereby putting pressure on public officials. This research uses a mixed-methods approach to explain the intricacies of media capture in Pakistan and its wider consequences for journalistic integrity and democratic government. It includes qualitative interviews with journalists and quantitative surveys of public perception.